Hybrid Leadership and Incivility in Healthcare - Sparks, Betsy; McCann, Jack (Journal of Leadership, Accountability and Ethics, 2024)
With a rise in incivility in the workplace, leadership is critical for today’s healthcare organizations. There are many leadership styles to consider for healthcare leaders. This research focuses on nine leadership and hybrid leadership styles to determine significant relationships to incivility among healthcare employees. We used the Vannsimpco Leadership Survey and Chung et al.’s Work Group Incivility scale to survey 174 healthcare employees. Our study found that managers need to know that one leadership style may not be the best and that a combination of styles may be needed in varying situations. We found that transformational and autocratic-transformational leadership styles reduced incivility between healthcare employees. Our study indicated that when a manager uses transformational leadership or a hybrid form of autocratic-transformational leadership, healthcare employees have less incivility.